PENGARUH KEKERAPAN MEMBACA SURAT KABAR TERHADAP KEMAMPUAN MEMAHAMI WACANA - Golda Mair (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
This study aims to determine the frequency of reading the newspaper,the ability to understand the discourse and influence the frequency of reading anewspaper on the ability to understand the discourse. The population in this studywere students of class X SMA Methodist 8 Medan Year 2009/ 2010 Learningtotaling 110 people. Samples were taken 30 people.The method used in this research is descriptive method. Data collectiontool used questionnaires and tests. The questionnaire used to collect the datafrequency of reading newspapers and essay tests used to collect data is the abilityto understand the discourse.Once the data is collected and analyzed the results of the study showedthat the states Incidence Reading Newspaper Methodist High School Class X 8Medan Year 2009/2010 Learning is at sufficient levels to an average value of 65,Ability Discourse Understanding Methodist High School Class X 8 field ofLearning 2009/2010 are at a high level with an average value of 68.5, and theEffect Frequency Reading the news letter to the ability of DiscourseUnderstanding Class X 8 Terrain Methodist high School Year 2009/2010 arelearning at a very strong level is 0.857.To test the hypothesis, used product moment correlation formula is 0.857Furthermore, in consultation with the db table r N-2 (30-2) = 28, r = db table for28 is 0.374. Thus rh  rt (0.857> 0.374), determination index obtained from thecalculation is 73.44%. So the influence of the frequency of reading the newspaperwith the ability to understand the discourse of class X SMA Methodist 8 MedanYear 2009/2010 Study of 73.44% means that the hypothesis (Ha) reads thefrequency of reading newspapers significantly affect the ability to understand thediscourse of class X SMA Methodist 8 Medan Year 2009/2010 Learningacceptable.